Special Modes of Gaps Overcoming in Civil Law - D. N. Polyakov (Сибирское юридическое обозрение)
The author reveals legal aspects of gaps overcoming in civil law in law enforcement practice. Analyzing the existing special ways of gaps overcoming the author pays special attention to the problem of judicial practice which is actually a constituent part of the Russian legal system, playing an important part of a legal source